PENGELOLAAN KONTEN MEDIA SOSIAL KORPORAT PADA INSTAGRAM SEBUAH PUSAT PERBELANJAAN - Mahmudah, Siti Muslichatul; Rahayu, Muthia (Jurnal Komunikasi Nusantara, 2020)
The use of social media continues to increase until now, one of is Instagram that commonly used at the corporate level. As in the type of shopping center company (Mall) that has a visitor with characteristics to find out all information related to the mall that he wants to visit through the mall's social media, Instagram. Therefore it requires the management of social media content to help the company's audience in getting information and become the communication media between the company and their audience. The theory used in this research is The Circular Model of Some by Regina Luttrell in his book Social Media How to Engage, Share, and Connect. From the results of the research note that in managing content on corporate social media instagram, the aspect of sharing begins with understanding the purpose of the use of social media platforms for corporates. Next to the optimize aspect, which is to make a posting schedule and use the features available on Instagram. The process of controlling or aspects of managing is also carried out by making media monitoring reports as a form of evaluation and accountability to company management. In the aspect of engaging, establishing good relations with the online community to get Instagram exposure on the content produced. Keywords: Social Media Management, Content, Instagram.